2019
DOI: 10.1097/dss.0000000000002262
|View full text |Cite
|
Sign up to set email alerts
|

Use of Lasers for Iron-Induced Accidental Tattoos: Experience at a Tertiary Referral Center

Abstract: BACKGROUND Awareness of accidental tattoos after iron injections with paravenous leakage is low. No larger patient cohorts have been analyzed. The lesions are a burden to the patients. The only known treatment is laser therapy. OBJECTIVE To characterize the clinical appearance and development of iron-induced tattoos and to demonstrate safe and efficient removal with quality-switched (QS) and picosecond lasers. MATERIALS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…One review assessed 29 patients who had reported accidental staining from iron infusions over a nineyear period. 13 Thirteen patients had laser therapy Box 3 Clinical features of iron extravasation [6][7][8][9][10][11][12][13]…”
Section: Management Of Iron Stainingmentioning
confidence: 99%
See 3 more Smart Citations
“…One review assessed 29 patients who had reported accidental staining from iron infusions over a nineyear period. 13 Thirteen patients had laser therapy Box 3 Clinical features of iron extravasation [6][7][8][9][10][11][12][13]…”
Section: Management Of Iron Stainingmentioning
confidence: 99%
“…12 Patients who experience iron extravasation resulting in staining may describe pain, swelling, and feelings of pressure or pricking at the infusion site. 13 Patients should therefore be told to notify staff of any of these symptoms ( Box 3 ). This is an important consideration for patients who do not understand English.…”
Section: Minimising Harmmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, however, there are scant data in the literature about the possible and most efficient therapeutic options. Treatments with qualityswitched (QS) lasers are reported in a few cases with different wavelengths: 532, 755 and 1,064 nm (6,7,(9)(10)(11)(12). QS lasers, developed in the 1980s, are efficient in the removal of exogenous and endogenous pigments, such as tattoos, as well as epidermal and dermal melanin lesions.…”
mentioning
confidence: 99%